IMPROVEMENT OF THE ION-PLASMA DUSTING METHOD OF THE INTERNAL COMBUSTION ENGINES’ VALVES BASING ON THE TOPOCOMPOSITE COVERINGS’ MULTIFRACTAL ANALYSIS - D. N. Korotaev; K. N. Poleshchenko; P. B. Grinberg; E. E. Tarasov (Вестник СибАДИ, 2018)
Introduction. Digital image and calculation of multifractal dimension spectra are carried out in the research basing on the investigation of the coatings’ topology, which are created by ion-plasma spraying on steel surfaces and used for internal combustion engine (ICE) valves.Results. Quantitative assessment of the structural changes received on the different power modes of ion-plasma dusting is executed in the article.Discussion and conclusion. It is concluded that complex indicators of multifractal dimensions could be used for forecasting and optimization of the ion-plasma processing modes for the purpose of anti-wear coatings on automobile parts at the repair process forming.